Instructional Strategies for Foreign Languages Learning: A Practical Approach of Mahmud Yunus’ Thought - Maulana, Mohammad Firman (Universitas Islam Negeri Raden Intan Lampung, 2020)
Mahmud Yunus’ thoughts about instructional strategies that he wrote in his book are rational and comprehensive enough to motivate students to learn. His strategies focus on fostering students’ self-confidence, independence, creativity, and courage to try to manifest themselves and to actualize themselves. This study tried to look further at how these instructional strategies were carried out in foreign language learning, such as English learning and Arabic learning. The method used in this research was literature research with data source triangulation. To collect the data and information, we used deductive thinking. A descriptive qualitative method was used to present the results of the study. The results of this study showed that the instructional strategies of Mahmud Yunus emphasized teaching patterns with a system of direct method, practical and collaborative learning. This approach is relevant in language teaching for both, beginners and intermediate levels. Therefore, educators and further research will be very good if they can apply Mahmud Yunus’ instructional strategy in language learning.